1974
DOI: 10.1084/jem.140.1.172
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Immune Responses in Vitro

Abstract: Although nonresponder, H-2s and H-2q, mice fail to develop GAT-specific PFC responses to GAT, they do develop GAT-specific PFC responses when stimulated by GAT complexed to an immunogenic carrier such as methylated bovine serum albumin. The studies described in this paper show that injection of nonresponder mice with GAT specifically decreases their ability to develop anti-GAT PFC responses to a subsequent challenge with GAT-MBSA. Addition of GAT to cultures of spleen cells from nonresponder mice also prevents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

1975
1975
1984
1984

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…In contrast, the F, crosses between GAT responders and nonresponders behaved as responders to GAT, in keeping with the dominant character of H-2-linked Ir genes, indicating that responder phenotypes are dominant over suppressor phenotypes (2,3). The other major conclusion from the strain distribution of GT-induced suppression ofGT-MBSA responses is that the Is gene(s) controlling these responses are coded for in the H-2 complex.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In contrast, the F, crosses between GAT responders and nonresponders behaved as responders to GAT, in keeping with the dominant character of H-2-linked Ir genes, indicating that responder phenotypes are dominant over suppressor phenotypes (2,3). The other major conclusion from the strain distribution of GT-induced suppression ofGT-MBSA responses is that the Is gene(s) controlling these responses are coded for in the H-2 complex.…”
Section: Discussionmentioning
confidence: 80%
“…To determine if suppression induced by GT is distinct from that induced by GAT, we compared the effect of immunization with GT and GAT in DBAA (H-29) and SJL (H2$) mice on the PFC responses to these copolymers complexed with MBSA. These strains were selected for the experiments because GAT stimulates GAT-specific T cells capable of suppressing GAT-MBSA PFC responses in both strains (3,5), whereas GT is able to suppress GT-MBSA responses in SJL, but not in DBA/1 mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies from our laboratory have shown that injection of GT or GAT into nonresponder mice bearing the H-2 d or H-2 q haplotype stimulate suppressor T cells capable of inhibiting antigen-specific IgG PFC responses to GT-MBSA or GAT-MBSA, respectively (5,12). The effect of GT preimmunization on the IgM and IgG PFC responses of BALB/c mice is shown in Table VI.…”
Section: Antigenic Suppression Of the Igm And Igg Pfc Responses Of Gamentioning
confidence: 99%
“…Previous studies from our laboratory demonstrated that immunization of nonresponder mice with GAT or GT stimulates the development of specific T cells capable of suppressing the primary IgG responses to GAT-MBSA (12) and GT-MBSA, respectively (5). The ability to elicit secondary IgM responses to these antigens permitted us to verify that such responses are also suppressed in nonresponder animals by preimmunization with the uncomplexed copolymers.…”
mentioning
confidence: 94%